Improving undergraduate biology students’ critical thinking skills through a case study-based free inquiry module - Qurrotul Anfa; Desi Nuzul Agnafia; Fitri Astriawati (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2023)
The free inquiry-based module supports independent research-based learning among undergraduate students. Adding case studies to the modules will encourage students to apply concepts to real-world situations to improve their thinking skills. Therefore, this study aims to improve the critical thinking skills of biology education students at Jambi University using case-study-based free inquiry modules. This study is Classroom Action Research (CAR) with the Kurt Lewin model, which consists of two cycles. The subjects of this study were 36 second-semester biology education students taking environmental science courses. The data collection techniques included questionnaires, critical thinking tests, and observation sheets. Data analysis techniques used quantitative descriptive analysis. Our findings indicated that critical thinking skills among undergraduate students in each cycle increased by an average of 23.01%. This means that the case-study-based free inquiry module successfully improves the critical thinking skills of biology education students.Abstrak Modul berbasis free inquiry mendukung pembelajaran berbasis penelitian secara mandiri pada mahasiswa. Sementara penambahan studi kasus pada modul akan mendorong mahasiswa untuk menerapkan konsep pada situasi nyata untuk meningkatkan keterampilan berpikir mereka. Oleh karena itu, penelitian ini bertujuan untuk melihat implikasi penggunaan modul free inquiry berbasis studi kasus terhadap peningkatan keterampilan berpikir kritis mahasiswa pendidikan biologi Universitas Jambi. Penelitian ini adalah Penelitian Tindakan Kelas (PTK) dengan model Kurt Lewin yang terdiri dari dua siklus. Partisipan penelitian ini adalah 36 mahasiswa pendidikan biologi semester dua yang mengambil mata kuliah ilmu lingkungan. Teknik pengumpulan data menggunakan angket, instrument test ketarmpilan berpikir kritis, dan lembar observasi. Teknik analisis data menggunakan analisis kuantitatif deskriptif. Hasil penelitian menunjukkan bahwa kemampuan berpikir kritis mahasiswa pada setiap siklus rata-rata meningkat sebesar 23,01%. Artinya penggunaan modul free inquiry berbasis studi kasus berhasil meningkatkan keterampilan berpikir kritis mahasiswa pendidikan biologi.